2013
DOI: 10.1021/jp408522m
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Energy Transfer From Vibrationally Excited CO2 Molecules: Cross Sections and Probabilities for Kinetic Modeling of Atmospheres, Flows, and Plasmas

Abstract: We present extended applications of an established theoretical and computational machinery suitable for the study of the dynamics of CO2+CO2 collisions, focusing on vibrational energy exchange, considered over a wide range of energies and rotational temperatures. Calculations are based on quasi-classical trajectories on a potential energy function (a critical component of dynamics simulations), tailored to accurately describe the intermolecular interactions, modeled by the recently proposed bond-bond semiempir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 65 publications
(89 reference statements)
1
14
0
Order By: Relevance
“…The exchange between bending and stretching contrasts with the decoupling of the asymmetric TABLE V. Probabilities and cross sections for the state-to-state vibrational transitions upon collision at E = 20.0 kcal/mol, n = 1, and rotational temper- stretching mode, which is a spectator with respect to the energy transfer even when n is relatively high (see Table IV, n = 9). A similar behavior has been observed in a previous work, 9 where the initial selective excitation of the bending mode was considered. This separability of stretching-bending and asymmetric stretching vibration modes seems to have an upper limit, since the asymmetric stretching excitation is found to occur with high probability for n = 11, as can it can be seen in Table VI, reporting cross sections and probabilities at E = 8 kcal/mol.…”
Section: A Vibrational Energy Transfer In Co 2 -Co 2 Collisionssupporting
confidence: 86%
See 1 more Smart Citation
“…The exchange between bending and stretching contrasts with the decoupling of the asymmetric TABLE V. Probabilities and cross sections for the state-to-state vibrational transitions upon collision at E = 20.0 kcal/mol, n = 1, and rotational temper- stretching mode, which is a spectator with respect to the energy transfer even when n is relatively high (see Table IV, n = 9). A similar behavior has been observed in a previous work, 9 where the initial selective excitation of the bending mode was considered. This separability of stretching-bending and asymmetric stretching vibration modes seems to have an upper limit, since the asymmetric stretching excitation is found to occur with high probability for n = 11, as can it can be seen in Table VI, reporting cross sections and probabilities at E = 8 kcal/mol.…”
Section: A Vibrational Energy Transfer In Co 2 -Co 2 Collisionssupporting
confidence: 86%
“…7,8 Accordingly, the systematic application of kinetic models, for both daily forecasts and research purposes in the above mentioned fields, and the need for growing accuracy and predictive character of them are fostering the production of detailed inelastic molecular collisions data to feed extended databases of state-to-state cross sections and rate coefficients. 9 In this context, carbon dioxide is a widespread studied molecule, being present in the Earth's and planetary atmospheres (as a major component in Venus and Mars). Its presence in the Earth's atmosphere is a cornerstone of the theories about the anthropic origin of global warming: being CO 2 a greenhouse gas, there is wide agreement that small enhanced concentrations of CO 2 can potentially alter the surface temperature and matter for climate.…”
Section: Introductionmentioning
confidence: 99%
“…The vibrational state of the linear CO 2 molecule is defined by three quantum numbers (see below), since one of them, corresponding to the vibrational angular momentum, is disregarded. This assumption has been discussed and motivated in a series of previous works on CO 2 , [25][26][27] where it was observed that the bending states with high rotational energy are unlikely and the energy associated with the vibrational angular momentum is negligible (see, e.g., Ref. [26], where the time evolution of the radial and angular energy associated with the bending has been considered in typical cases).…”
Section: Full Paper Wwwc-chemorgmentioning
confidence: 97%
“…This assumption has been discussed and motivated in a series of previous works on CO 2 , [25][26][27] where it was observed that the bending states with high rotational energy are unlikely and the energy associated with the vibrational angular momentum is negligible (see, e.g., Ref. [26], where the time evolution of the radial and angular energy associated with the bending has been considered in typical cases). According to this scheme, each bunch of trajectories is identified by temperatures T and T rot ( 5 T), and by the initial vibrational quantum numbers of the colliding CO 2 and N 2 molecules.…”
Section: Full Paper Wwwc-chemorgmentioning
confidence: 97%
“…Quantization can be achieved using a separable normal mode harmonic model because the energies corresponding to each normal mode can be directly calculated by projecting the classical phase-space vector of the system final states onto the normal mode vector basis. The rotational compontent of the energy stored in the two bending degrees of freedom can then be extracted by giving the two corresponding normal coordinates a representation in terms of polar coordinates (as stated above, this rotationa component is neglected in our calculations) [58]. Although this simple method may lead to an inaccurate labeling of the vibrational states for highly excited molecules, this is usually of negligible impact when the quantum states lie well below the strong anharmonic region of the potential.…”
Section: A Molecule-molecule Systemmentioning
confidence: 99%